Kesepakatan Etik dan Interpersonal dalam Evaluasi Program Pendidikan - Sri Wahyuningsih; Fadriati (STAI Terpadu Yogyakarta, 2022)
Evaluation of educational programs aims to find improvements needed in education. In practice, program evaluation also has a political aspect that needs to be paid attention to by the evaluator and the participants being evaluated. In addition, there is also an ethical agreement and interpersonal agreement in program evaluation, which is part of the code of ethics in carrying out evaluation activities. The purpose of this article is to provide an explanation of the importance of a code of ethics and political aspects in the implementation of educational program evaluation. The research method used is library research, where the author collects information related to the code of ethics and political aspects in the implementation of the evaluation of educational programs. The results of the study stated that there are several factors that influence ethics and interpersonal in the evaluation of education, namely religion that is believed, morals that develop in culture, educational treatment, messages in the mass media and environmental situations.